Efektivitas Pelaksanaan Musyawarah Perencanaan Pembangunan Kecamatan (Studi Kasus Di Kecamatan Batang Masumai Kabupaten Merangin Provinsi Jambi Tahun 2017-2018) - Arif Hidayat; Melinda Noer; Erwin (Jurnal Niara, 2022)
The implementation of the sub-district Musrenbang is a very important series of planning processes that become the subject of discussion in the district musrenbang proposals so that the district musrenbang discussions are the aspirations or wishes of the community, but in Batang Masumai sub-district there are still many proposals that are not accepted and are not in accordance with the development priorities of the district government. Therefore, researchers conducted a study on the Effectiveness of Implementation of District Development Planning Deliberations (Case Study in Batang Masumai District, Merangin Regency, Jambi Province, 2017-2018). In this study using the theory of effectiveness with three indicators, namely accountability, transparency and participation. Data collection techniques using interview, observation and documentation techniques and data analysis techniques using data collection techniques, data reduction, data presentation and drawing conclusions. The results of the research are that (1) The mechanism for implementing the development planning deliberations of the Batang Masumai sub-district in the last two years, 2017 and 2018 uses a different legal basis due to changes in the legal basis. (2) the ineffectiveness of the Batang Masumai sub-district development planning deliberation in 2017-2018 seen from the participation indicator that the participants of the Batang Masumai sub-district development planning deliberation decreased from 2017 to 2018. Judging from the accountability/accountability indicator that the implementation of the sub-district development planning deliberation was not carried out fully. Judging from the transparency indicator that it has not been fully implemented in the Batang Masumai sub-district development planning deliberations in 2017 and 2018.